The dynamic game when the interests of players coincide - Vakrinienė, S. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. П. Вакринене. Динамическая игра, когда интересы игроков совпадают S. Vakrinienė. Dinaminis lošimas, kai lošėjų interesai sutampa